Modulation of Interleukin-1 and Toll-like receptor signalling by the Vaccinia virus protein A52R - Maloney, Geraldine (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2005)
Vaccinia virus (VV) has many m echanisms to suppress and modulate the host im mune response. Given the role of Toll-like receptors (TLRs) and interleukin 1 (IL-1) in immunity, it was possible that VV would have mechanisms to antagonise these host proteins. Indeed, the VV protein A52R was previously shown to act as an inhibitor of NFkB signalling by IL-1 and TLR4. In this present study A52R is shown to inhibit the activation of NFkB by IL-1 and multiple TLRs, including TLRS, a receptor for viral RNA. Co-im munoprecipitation studies had previously revealed that A52R interacted with both TRAF6 and IRAK2. Here, the interaction between A52R and IRAK2 was shown to be sufficient for maximal NFkB inhibition. In addition, data is also shown for a role for IRAK2 in TLR3 signalling. Evidence is shown for a functionally distinct role for A52R from another VV TLR antagonist, A46R. A52R had no inhibitory effect on TLR3-induced interferon regulatory factor (IRF) 3 activation or signaling by IRF5 or 1RF7 activation in comparison with the potent inhibition of these signals by A46R.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin